1939
DOI: 10.1152/ajplegacy.1939.126.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Weight and Water Content of the Uterus of the Normal Adult Rat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0
6

Year Published

1945
1945
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 0 publications
9
39
0
6
Order By: Relevance
“…This was highest in early pro-oestrus and lowest in late di-oestrus. This change is similar to that described by Astwood (1939) but was not apparently found by Morgan (1963), nor by ourselves, using the Wistar strain. It is also to be noted that the content of water/unit DNA changed significantly, being highest at pro-oestrus and lowest in di-oestrus, changes which possibly reflect an increased water content/cell.…”
Section: Discussionsupporting
confidence: 91%
“…This was highest in early pro-oestrus and lowest in late di-oestrus. This change is similar to that described by Astwood (1939) but was not apparently found by Morgan (1963), nor by ourselves, using the Wistar strain. It is also to be noted that the content of water/unit DNA changed significantly, being highest at pro-oestrus and lowest in di-oestrus, changes which possibly reflect an increased water content/cell.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests either that the uterine mucosa is more permeable to luminal K+ during late prooestrus tban during oestrus, or that the clearance of ''-K from tbe uterus during late prooestrus is less than in oestrus. Although the exact time of increased oestrogen secretion during the rat's oestrous cycle has not been measured directly, Astwood (1939) has suggested that the short duration of increased water content in the uterus whicb occurs during prooestrus is a reflection of a brief period of oestrogen secretion just prior to prooestrus. The work of Jensen and Jacobson (1962) has shown that rat uterine tissues retain and continue to bind injected oestradiol for about 6 hrs.…”
Section: Discussionmentioning
confidence: 99%
“…This was true if the following two conditions were satisfied: (1) the turnover of uterine fluid had reached a steady state, i.e., the '•-'K was instilled when no net transfer of K+ was occurring. This period corresponds to the "plateau" of uterine fluid turnover (Astwood, 1939) which begins during late prooestrus. (2) The specific activity of the solution introduced into the lumen was high, so that the ''^K transferred into the uterine wall, in exchange for endometrial K+, does not significantly alter the specific activity of the luminal fluid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations